2010
DOI: 10.2105/ajph.2009.160184
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Breast Cancer Diagnosis and Initiation of Treatment in the National Breast and Cervical Cancer Early Detection Program, 1996–2005

Abstract: Women screened by the NBCCEDP received diagnostic follow-up and initiated treatment within preestablished program guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 44 publications
4
94
3
Order By: Relevance
“…3,5 Keeping the wait times between diagnosis and surgery below 60 days is considered an important measure of quality of care as well. [36][37][38] Two recent studies specifically examined surgical delay and predictors associated with it; only one of the studies included race and reported significant differences. 5,39 Similarly, AAs in our study were more likely than whites to experience surgical delay after accounting for differences in their sociodemographic and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Keeping the wait times between diagnosis and surgery below 60 days is considered an important measure of quality of care as well. [36][37][38] Two recent studies specifically examined surgical delay and predictors associated with it; only one of the studies included race and reported significant differences. 5,39 Similarly, AAs in our study were more likely than whites to experience surgical delay after accounting for differences in their sociodemographic and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additionally, Richardson et al 16 examined the timeliness of breast cancer diagnosis and treatment in the NBCCEDP and also found that minority women had longer median times to diagnosis of breast cancer than did white women. There may be multiple explanations for these findings, including individual characteristics, miscommunication of results, provider characteristics, or the healthcare facilities where minorities receive care.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Breast and Cervical Cancer Early Detection Program (NBCCEDP) benchmark, the time frame between identification of any suspicious mammogram screening test and diagnosis should not exceed 60 days and maximum another 60 days till initiation of treatment [7].…”
Section: Introductionmentioning
confidence: 99%